Impact of the Chuom model on aquatic resources and water environment in Cau Hai Lagoon and Nay Lagoon, Hue City - Lê, Công Tuấn; Nguyễn Văn, Huệ (Hue University Journal of Science: Natural Science, 2025)
This research assesses the impact of the Chuom model on the aquatic resources and water environment to serve as a basis for sustainable use of aquatic resources. This model is based on a traditional fishing mode called Chuom or Cha Rao in Vietnam and is used in both freshwater (Nay Lagoon) and brackish water (Cau Hai Lagoon). The results show that the model is effective in attracting fish species. The number of economic fish species inside the Chuom area is larger than that outside, with the Cau Hai Lagoon having nine species against five species and the Nay Lagoon having 13 species against 11 species. The model also increases the fish mass and the density of zooplankton inside the Chuom. Water quality parameters such as pH, NH4/NH3, and DO in the Chuom area are similar to those outside. It is necessary to have an official program to develop the Chuom model in the localities.